Comparison between catgut endoloop versus vicryl endoloop in laparoscopic appendicular stump closure - Mithari, Mrunal; G., Sadhan; Merlyn M., Rupa; M., Sriram Bhat (International Journal of Research in Medical Sciences, 2025)
Background: Laparoscopic appendectomy has become the standard of care for acute appendicitis, offering numerous advantages over open surgery. The closure of the appendicular stump remains a critical step in this procedure, with various techniques available. This study aimed to compare the efficacy and outcomes of catgut versus vicryl endoloops in appendicular stump closure. Methods: A prospective observational study was conducted at tertiary care hospitals in Mangalore from March 2022 to March 2024. Thirty-five patients undergoing laparoscopic appendectomy were included and divided into catgut (n=18) and vicryl (n=17) endoloop groups. Parameters evaluated included operative time, hospital stay duration, post-operative complications, and follow-up outcomes. Results: The mean operative duration was comparable between groups (catgut: 1.2±0.4 hours, vicryl: 1.4±0.6 hours, p>0.05). The catgut group demonstrated significantly shorter hospital stays (3.0±0.8 versus 4.1±0.8 days, p<0.05). Post-operative complications were similar between groups, with pain being the most common (catgut: 50%, vicryl: 41.2%). Early oral intake was achieved in 60% of patients by post-operative day one. Follow-up showed good recovery in 71.4% of patients, with no reported cases of stump appendicitis among those who completed follow-up. Conclusions: Both catgut and vicryl endoloops demonstrate comparable safety and efficacy in laparoscopic appendicular stump closure. While catgut endoloops showed advantages in hospital stay duration, both methods proved reliable with similar complication rates. The choice between materials can be based on surgeon preference and institutional protocols without compromising patient outcomes.